Rasionil Generasi Z Memilih Kolam Retensi Boulevard Kota Kendari Sebagai Fitur Olahraga Unggulan - Hamid, Nisrina; Rabbani, Inayah Abdillah; Lapau, Fitri (Fakultas Ekonomi dan Bisnis Universitas PGRI Semarang, 2024)
Generation Z has a different character from previous generations who rely heavily on technology in their development and growth, including getting digital-based references or information, including in deciding on choices to exercise. This study aims to determine the effect of facility variables, electronic word of mouth (e-wom) as a rational aspect of generation Z choosing the Kendari City boulevard retention pool as a superior sports feature using the SEM PLS approach with a sample size of 170 respondents using purposive sampling method with criteria, namely generation Z aged 12-28 years, and at least 2 times have exercised at the Kendari City boulevard retention pool. The results showed that the facility construct, e-wom had a positive and significant effect on the decision to choose the Kendari City boulevard retention pool, while the healty lifestyle construct had no positive and significant effect. The results of the R-Square value indicate a very strong correlation between facilities, e-wom and healty lifestyle in the selection decision of 0.997. The Adjusted R-Square value of 0.997 indicates that the exogenous variables are able to explain 99.7% of the endogenous variables while 0.3% is explained by other variables not examined in this study. Keywords: Electronic word of mouth;healty lifestyle; facilities;election decision, Z generation.